The future of design : global product innovation for a complex world - Justice, Lorraine , 1955- (Nicholas Brealey Publishing, 2019)
"Author Lorraine Justice, an internationally-recognized product design expert and consultant to companies like Microsoft, Disney and Levis, shares the ten global factors that directly impact product design success or failure. When these factors are combined or lacking, they have a direct impact on a product's ability to delight consumers and catch on, or rankle them and fizzle out"-- Provided by publisher